THE ROLE OF SCENARIO-BASED LEARNING IN TEACHER PREPARATION FOR FOREIGN LANGUAGE EDUCATION (Western European Journal of Linguistics and Education, 2024)
This article explores the role of scenario-based learning (SBL) in foreign language teacher education, highlighting its ability to bridge the gap between theoretical knowledge and realworld classroom practice. Drawing on key educational theories such as experiential learning, reflective practice, and situated cognition, the article demonstrates how SBL helps future educators develop essential skills in classroom management, adaptive problem-solving, and reflective practice. By engaging with authentic teaching scenarios, prospective teachers can better understand and apply pedagogical theories, preparing them for the complex challenges of foreign language teaching.